Revision of the Neotropical genus Eoneria Aczél (Diptera: Neriidae) with description of a new species from Colombia - Sepúlveda, Tatiana A.; Wolff, Marta I.; de Carvalho, Claudio J. B. (Zootaxa, 2013)
Here we revise Eoneria Aczél, 1951, a small genus of flies in the Neriidae, previously known from two species from Argentina. We describe a new species, E. aczeli Sepúlveda & Carvalho from Colombia, provide new records from Brazil, a distribution extension from Argentina and a new genus diagnosis, as well as an identification key based on adult morphology.